Akap5 links synaptic dysfunction to neuroinflammatory signaling in a mouse model of infantile neuronal ceroid lipofuscinosis - Koster, Kevin P.; Fyke, Zach; Nguyen, Thu T. A.; Niqula, Amanda; Noriega-González, Lorena Y.; Woolfrey, Kevin M.; Dell’Acqua, Mark L.; Cologna, Stephanie M.; Yoshii, Akira (Frontiers in Synaptic Neuroscience, 2024)
Palmitoylation and depalmitoylation represent dichotomic processes by which a labile posttranslational lipid modification regulates protein trafficking and degradation. The depalmitoylating enzyme, palmitoyl-protein thioesterase 1 (PPT1), is associated with the devastating pediatric neurodegenerative condition, infantile neuronal ceroid lipofuscinosis (CLN1). CLN1 is characterized by the accumulation of autofluorescent lysosomal storage material (AFSM) in neurons and robust neuroinflammation. Converging lines of evidence suggest that in addition to cellular waste accumulation, the symptomology of CLN1 corresponds with disruption of synaptic processes. Indeed, loss of Ppt1 function in cortical neurons dysregulates the synaptic incorporation of the GluA1 AMPA receptor (AMPAR) subunit during a type of synaptic plasticity called synaptic scaling. However, the mechanisms causing this aberration are unknown. Here, we used the Ppt1-/- mouse model (both sexes) to further investigate how Ppt1 regulates synaptic plasticity and how its disruption affects downstream signaling pathways. To this end, we performed a palmitoyl-proteomic screen, which provoked the discovery that Akap5 is excessively palmitoylated at Ppt1-/- synapses. Extending our previous data, in vivo induction of synaptic scaling, which is regulated by Akap5, caused an excessive upregulation of GluA1 in Ppt1-/- mice. This synaptic change was associated with exacerbated disease pathology. Further, the Akap5- and inflammation-associated transcriptional regulator, nuclear factor of activated T-cells (NFAT), was sensitized in Ppt1-/- cortical neurons. Suppressing the upstream regulator of NFAT activation, calcineurin, with the FDA-approved therapeutic FK506 (Tacrolimus) modestly improved neuroinflammation in Ppt1-/- mice. These findings indicate that the absence of depalmitoylation stifles synaptic protein trafficking and contributes to neuroinflammation via an Akap5-associated mechanism.